The Diversity of the Dragonfly of Orthetrum Genus in Protected Area of Mount Prau, Central Java Indonesia - Setyawati, Siti Mukhlisoh; Puwowidodo, Puwowidodo; Huda, Muh. Miftahul; Dewi, Bita Afriyanti (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2017)
Dragonfly of the genus Orthetrum is a dragonfly of the Lebullidae family. This dragonfly has a variety of types of morphological structure, body color, distribution and habitat. Habitat dragonfly of the genus Orthetrum is quite extensive, especially around lowland to upland waters. Protected Forest Mount Prau Central Java, is a rainforest that has a water flow appropriate for life dragonflies. It allows the Dragonflies of all kinds to live and thrive in the environment, including Orthetrum. This research was conducted to find out the types of Orthetrum that can be found in Protected Forest Area of Mount Prau, Central Java. Determination of sampling is done along the river flow at 3 stations with total sub plot of sample as much as 12 point, starting from near settlement flow up to 2100 m toward waterfall source. The results of the sample analysis showed morphological variations in the structure of the thorax and abdomen as well as the color variations and patterns on the thorax, abdomen, and wings. Identification of the dragonfly obtained four types of dragonfly Orthetrum with variations on the sex, the male and female sabina Orthetrum, Orthetrum caffrum males. Orthetrum testaceum male, male and female pruinosum Orthetrum, and Orthetrum male and female glaucum. Â©2017 JNSMR UIN Walisongo. All rights reserved.